Chinese Loan to Africa in the lens of Pragmatism Economics - Widjanarko, Yeremia Nicolaus (Jurnal Hubungan Internasional, 2023)
This paper examined the reasons behind China's decision to provide loans to African states, a group that had been traditionally been considered not creditworthy by MDBs. Utilizing a descriptive-explorative research method, primary to secondary data ranged from 1999 to 2022, and the framework of economic pragmatism, this paper analyzed and found some pragmatic implications. The findings concluded that China's lending strategy was mostly motivated by a pragmatic approach aimed at gaining early access to African markets, securing vital natural resources, assisting Chinese corporations, and creating economic dependence. China's loans were used to fund infrastructure projects, reducing logistics costs for Chinese businesses and diversifying foreign exchange reserves. This paper posited that China's policy was driven by empirical facts, adaptiveness to global economic conditions, and a focus on concrete economic benefits, such as increasing imports from China and gaining access to natural resources. Therefore, this paper describes China's efforts to strengthen its influence and obtain tangible economic advantages through its lending practices in Africa   Keywords: Africa, China, Development Loan, Economic Gains, Political-Economy